Supervisor Support and Work-Family Practices: A Systematic Review - Daniela Geraldes; Maria José Chambel; Vânia Sofia Carvalho (Societies)
In recent decades, in response to changes in work dynamics, demographics, and technological advancements, organizations have sought to implement practices that facilitate transitions between work and family—so-called work-family practices. Previous research has focused on identifying antecedents for a more positive work-family relationship, employees’ well-being, and positive organizational outcomes. Nevertheless, the development of this research framework over the decades has brought a main conclusion and concern: the availability of these practices is not a measure of organizational success and, to some extent, is dependent on the supportive behaviors of supervisors. To address the growing interest in this topic, a systematic review was conducted to qualitatively analyze the relationship between work-family practices and supervisor support, as well as their subsequent impact on employees and organizations. Following a PRISMA methodology, this review examined 39 articles (40 studies) and corroborated the positive and essential role of supervisor support in enhancing the effectiveness of work-family practices. The findings further clarified its influence on employee well-being and health, workplace attitudes (e.g., commitment, job satisfaction, turnover intention), and the work-family relationship (e.g., conflict and enrichment). Consequently, supervisor support proved imperative for employees and organizational contexts to benefit from work–family practices, going beyond their provision by organizations. Therefore, this research is the first systematic review focusing on recognizing and confirming the importance of work-family practices and supervisor support as foundational components of a family-supportive work environment. Theoretical and practical implications, as well as future research paths, will be discussed.